2021
DOI: 10.2147/opth.s327660
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Age, Postoperative Refraction, and Pre- and Postoperative Pupil Size on Halo Size and Intensity in Eyes Implanted with a Trifocal or Extended Depth-of-Focus Lens

Abstract: Halos are a chief source of patient dissatisfaction after multifocal intraocular lens (IOL) implantation. The primary purpose of this study was to investigate the influence of age, postoperative refraction, and pre-and postoperative pupil size on postoperative halo size with a trifocal diffractive IOL (AcrySof IQ PanOptix) and extended depth-of-focus (EDOF) IOL (TECNIS Symfony) to determine whether these factors could predict postoperative halo size. Patients and Methods: This single-center, open-label study c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
(54 reference statements)
0
9
1
Order By: Relevance
“…Halo formation results from the superimposition of these out-of-focus images on the focused image projected on the retina [ 25 ]. Teshigwara et al [ 26 ] showed that the change in halo size and intensity of a diffractive trifocal and a hybrid multifocal-EDOF IOLs over time should be considered during treatment planning, and they suggest that age, target refraction, and pre-operative pupil size might be predictive factors for halo size. Rementería-Capelo et al [ 27 ] reported that the mean halo effect after diffractive trifocal implantation was lower when no residual refractive error is induced, with a higher halo perception with defocus, being similar both for negative and positive defocus.…”
Section: Discussionmentioning
confidence: 99%
“…Halo formation results from the superimposition of these out-of-focus images on the focused image projected on the retina [ 25 ]. Teshigwara et al [ 26 ] showed that the change in halo size and intensity of a diffractive trifocal and a hybrid multifocal-EDOF IOLs over time should be considered during treatment planning, and they suggest that age, target refraction, and pre-operative pupil size might be predictive factors for halo size. Rementería-Capelo et al [ 27 ] reported that the mean halo effect after diffractive trifocal implantation was lower when no residual refractive error is induced, with a higher halo perception with defocus, being similar both for negative and positive defocus.…”
Section: Discussionmentioning
confidence: 99%
“…Halo intensity was significantly higher with Symphony than with PanOptix. 11 In addition, Böhm et al didn't show a significant difference in the percentage of patients perceiving halos compared to PanOptic, AT LISA tri, and Symphony. Still, the intensity of haloes was significantly higher in the PanOptic and AT LISA groups without significant differences.…”
Section: Discussionmentioning
confidence: 96%
“…7 However, only a few comparative studies of this model versus other equivalents are available in the literature. [8][9][10][11][12] With conflicting results, six head-to-head studies evaluated the AcrySof IQ PanOptix and the AT LISA tri 839 MP IOL (Supplemental Table 1). [12][13][14][15][16][17][18] The reduced accuracy of near, distant, and intermediate VA assessment using optotypes is widely established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 In multifocal and extended depth-of-focus IOLs, pupil size (OCT) positively correlated with halo size and patients with small pupils (autorefractor with integrated grid scale) presented with less photic phenomena and higher visual satisfaction after surgery with a further multifocal IOL. 33,34 Therefore, pupil size still remains a controversial, but important topic to refractive procedures. A fitting eye mask, binocular pupil size measurements with relaxed accommodation would be a further approach to ensure precise measurements especially under scotopic and low mesopic conditions.…”
Section: Discussionmentioning
confidence: 99%